Integrating statistical and hydrological models to identify implementation sites for agricultural conservation practices. (October 2015) - Giri, Subhasis; Nejadhashemi, A. Pouyan; Zhang, Zhen; Woznicki, Sean A.
Abstract: Watershed models are scarcely used by watershed managers due to their complexity. This study facilitates information transfer by introducing simpler techniques related to easily obtained watershed characteristics, including distance to the watershed outlet and stream order. The Soil and Water Assessment Tool (SWAT) was calibrated for the Saginaw River Watershed, Michigan. Five agricultural best management practices (BMPs) were implemented in SWAT one at a time in each subbasin. Five statistical models were used to determine the pollution reduction at the watershed outlet using distance and BMP type, with results suggesting that a mixed effects model (model 5) was optimal. This model included subbasin as a random effect, while distance to watershed outlet and BMP type were fixed effects. Native grass and strip cropping were the most effective BMPs for reducing sediment and nutrient transport. Subbasins containing stream orders 1–3 were ideal for BMP implementation throughout the watershed. Highlights: Novel techniques identify the best location for conservation practice installation. Trellis plots help to determine the optimal distance to maximize pollution reduction. Surface plots were created to visualize watershed response to pollution reduction. This study helps decision makers and stakeholders in local and watershed-scale planning.